Synthesis of C3, C5, and C7 pregnane derivatives and their effect on NMDA receptor responses in cultured rat hippocampal neurons - Stastna, Eva; Chodounska, Hana; Pouzar, Vladimir; Kapras, Vojtech; Borovska, Jirina; Cais, Ondrej; Vyklicky, Ladislav (Steroids, 2009)
The synthesis of several novel 5alpha- and 5beta-20-oxo-pregnane derivatives substituted in the position 3 and 7 of the steroid skeleton is described. Activity of synthesized compounds was studied in voltage-clamped cultured rat hippocampal neurons. Substituted derivatives inhibited NMDA-elicited neuronal activity. The relationship between biological activity and structure is discussed.
Keywords: Patch-Clamp Techniques; pregnany; Electric Conductivity; metoda terčíkového zámku; Inhibitory Concentration 50; neurony; elektrická vodivost; krysa rodu Rattus; Hippocampus; kultivované buňky; Animals; zvířata; Neurons; Rats; Pregnanes; Cells, Cultured; inhibiční koncentrace 50; Receptors, N-Methyl-D-Aspartate; receptory N-methyl-D-aspartátu; hipokampus